2022
DOI: 10.3390/nano12050858
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Bioactivity Evaluation of Polyoxymethylene Copolymer/Nanohydroxyapatite-g-Poly(ε-caprolactone) Composites

Abstract: In this work, nanohydroxyapatite (HAp) was functionalized with poly(ε-caprolactone) (PCL), using 1,6-hexamethylene diisocyanate (HDI) as a coupling agent, and then incorporated into the polyoxymethylene copolymer (POM) matrix using the extrusion technique. The obtained POM/HAp-g-PCL composites were investigated using FTIR, DSC, TOPEM DSC, and TG methods. Mechanical properties were studied using destructive and non-destructive ultrasonic methods, wettability, and POM crystallization kinetics in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…On the non-modi ed POM surface (Fig. 2A) the WCA value is equal to 78.2 degrees, which is consistent with the literature results [40][41][42]. Figure 2B, 2C and 2D show the samples from each series with the largest obtained effect.…”
Section: Resultssupporting
confidence: 90%
“…On the non-modi ed POM surface (Fig. 2A) the WCA value is equal to 78.2 degrees, which is consistent with the literature results [40][41][42]. Figure 2B, 2C and 2D show the samples from each series with the largest obtained effect.…”
Section: Resultssupporting
confidence: 90%
“…Typical examples of the changes in the wettability induced by the plasma modification are illustrated in Figure 2. On the non‐modified POM surface (Figure 2A) the WCA value is equal to 78.2 degrees, which is consistent with the literature results [40–42] . Figure 2B, 2 C and 2D show the samples from each series with the largest obtained effect.…”
Section: Resultssupporting
confidence: 89%
“…On the non-modified POM surface (Figure 2A) the WCA value is equal to 78.2 degrees, which is consistent with the literature results. [40][41][42] Figure 2B, 2 C and 2D show the samples from each series with the largest obtained effect. It can be observed that the contact angle values increased more than twice.…”
Section: Resultsmentioning
confidence: 99%
“…[44] The fingerprint region (500-1500 cm À1 ) of IR spectrum in Figure 1 also clearly showed all the characteristic peaks of pure POM. [45][46][47] The incorporation of SWN into the POM nanocomposites did not influence the FTIR spectrum, which there was not any peak shifting, appearance of new peak or disappearance of old peak observed. This shows that there was no strong chemical interaction between SWN and POM chains during the melt extrusion, thus it is suggested that physical interaction was mandatory in altering the properties of POM/SWN nanocomposites.…”
Section: Structural Characterization Of Pom Nanocompositesmentioning
confidence: 99%